2013
DOI: 10.1016/j.celrep.2013.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Aurora A Kinase Regulates Mammary Epithelial Cell Fate by Determining Mitotic Spindle Orientation in a Notch-Dependent Manner

Abstract: Cell fate determination in the progeny of mammary epithelial stem/progenitor cells remains poorly understood. Here, we have examined the role of the mitotic kinase Aurora A (AURKA) in regulating the balance between basal and luminal mammary lineages. We find that AURKA is highly expressed in basal stem cells and, to a lesser extent, in luminal progenitors. Wild-type AURKA expression promoted luminal cell fate, but expression of an S155R mutant reduced proliferation, promoted basal fate, and inhibited serial tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 54 publications
4
55
0
Order By: Relevance
“…One recent study revealed exclusively planar cell divisions within the basal, cap cell layer of the TEB, with no observed contribution of basal cells to the internal, body cell compartment (Taddei et al, 2008). Another recent study observed a minority of vertical basal cell divisions in stratified TEBs during ductal elongation (Regan et al, 2013). Both of these studies were based on the analysis of fixed sections of the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study revealed exclusively planar cell divisions within the basal, cap cell layer of the TEB, with no observed contribution of basal cells to the internal, body cell compartment (Taddei et al, 2008). Another recent study observed a minority of vertical basal cell divisions in stratified TEBs during ductal elongation (Regan et al, 2013). Both of these studies were based on the analysis of fixed sections of the mammary gland.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Aurora-A is implicated in spindle orientation in asymmetric cell divisions in Drosophila [34] via phosphorylation of Pins [35]. Excess Aurora-A can also influence the spindle orientation and the cell fate in human mammary epithelium stem/progenitor cells [36]. In our time-lapse assays using a U2OS cell line with fluorescent MTs, we actually visualized spindle rotation movements: thus, Aurora-A activity is required for pathways that determine the mitotic spindle orientation, raising the possibility that Aurora-A inhibition influences the fate of asymmetrically dividing cells and/or tissue architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, analysis of partitioning of the cell fate determinant Numb showed that PKH26 hi cells in the MaSC/basal population predominantly divide through asymmetric division (Cicalese et al 2009). In addition, b1 integrin and a Notch-dependent Aurora A pathway have been implicated in regulating the cell division axis in the mammary gland (Taddei et al 2008;Regan et al 2013). The recent evaluation of mice harboring an inducible histone 2b (H2B) promoter linked to a GFP reporter (K5tTA-H2b-GFP) (Dos Santos et al 2013) revealed a small subset (0.2%) of slowly cycling H2b-GFP hi cells within the MaSC/basal population.…”
Section: Evidence For Slow-cycling and Quiescent Stem Cellsmentioning
confidence: 99%